Gozdni rastiščni tipi Slovenije - Rozman, Andrej (Gozdarski vestnik, 2025)
This article provides a comprehensive overview of the forest vegetation types (FST) of Slovenia, including their ecological, vegetation, site, vegetation and management analysis. Based on extensive spatial, phytocenological and forest management data, the distribution of 78 FSTs in Slovenia and their occurrence in phytogeographic zones, altitudes and ecological gradients are presented. Species diversity, site characteristics, climatic conditions, site productivity and threats from weather and biotic disturbances are presented. Based on the analyses, management guidelines and risks for individual FSTs are also presented. The paper serves as a methodological framework for further detailed descriptions of individual FSTs, which will be published in the next issues of the Forestry Journal.
Keywords: biodiversity; ecological characteristics; ekološke značilnosti; forest vegetation types; gozdni rastiščni tipi; sonaravno gospodarjenje z gozdovi; sustainable forest management; vegetacija; vegetation; vrstna pestrost